Die hohen deutschen Kirchtürme - Born, Walter (Hildesheim Lax, 1979)
U.a. Magdeburger Dom
Enth. Register. - Bibliographie: S. 247 - 249
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Geschichte ; 1340-1980